Performance Analysis and Evaluation of Disk Scheduling Algorithms in Operating Systems - Somaya Salam Omar; Ali Salam Alatrsh; Noura M. Alkurri; Noureddin Y. S. Elhaj (Journal of Scientific and Human Dimensions, 2026)
Optimal management of hardware resources is a critical cornerstone of modern operating system design. The efficiency of secondary storage systems, particularly Hard Disk Drives (HDDs), directly influences overall system performance, heavily relying on key metrics such as access time and data transfer bandwidth. In contemporary multiprogramming environments, multiple Input/Output (I/O) requests simultaneously pool in the system memory. When the disk drive is occupied, a specialized scheduling mechanism is required to structure and manage the request queue effectively. This paper presents a comprehensive analytical and comparative study on the dynamic performance of six prominent disk scheduling algorithms: First-Come, First-Served (FCFS), Shortest Seek Time First (SSTF), SCAN, Circular SCAN (C-SCAN), LOOK, and Circular LOOK (C-LOOK). The methodology relies on evaluating performance efficiency by calculating the total head movement (measured in tracks). The quantitative results reveal significant variations in seek optimization and response times, providing developers and system architects with distinct benchmarks to select the optimal algorithm based on system workloads and operational requirements
Keywords: Disk Scheduling; Operating Systems; Seek Time; Request Queue; Elevator Algorithm; Hardware Optimization